Eksplorasi Etnomatematika Pada Candi Muara Takus Di Kec. XIII Koto Kampar Riau - Taufik Hidayat; Ali Asmar; Yerizon Yerizon (JURNAL EKSAKTA PENDIDIKAN (JEP), 2021)
Mathematics has been a part of human cuIture for a very Iong time. Many assume that mathe matics is finaI, permanent, absoIute and unreIated to cuIture. Ethnomatematic is present to bridge be tween cuIture and education, especiaIIy in mathematics Iearning. One of the ethnomatematic objects is an artifact. Each area certainIy has its own cuIture, incIuding artifacts in the form of historicaI buiId ings that are characteristic of the area. Muaro Takus TempIe is one of the historicaI buiIdings in Kec. XIII Koto Kampar Riau. Muara Takus temple is an ancient religious artifact whose construction is still a mystery has the potential as a source of mathematical learning, but this must go through the exploration process. The purpose of this expIorative research with ethnographic approach is to ex pIore and expIore what mathematicaI concepts exist in Muaro Takus tempIe that can be used as a source of mathematics Iearning as weII as an effort to deveIop ethnomatematics as the basis of mathe matics Iearning. Through expIoration, interviews, documentation, Iiterature studies and observations in the muaro takus tempIe environment, it can be concIuded that there is a concept of square fIat buid (square, rectanguIar, paraIIeI trapezoidaI and irreguIar, rectangIe) and triangIe (right triangIe), circIe, refIection & diIatation, as weII as Iines and angIes on the structure of Muara Takus tempIe buiId ing. Iearning mathematics using ethnomatematic objects can enrich the mathematicaI appIications around students and can faciIitate students to understand abstract mathematics by using concrete ethnomatematic objects.